Mata Hari (Greta Garbo collection, 2005)
"Mata Hari: the name breathes mystery, intrigue and sexual allure. Who better to play the notorious World War I spy than Greta Garbo, the enigmatic, exquisite screen icon called The Swedish Sphinx? Garbo is mesmerizing as the dancer-turned-German secret agent in a wartime Paris seething with secrets and betrayal. The notable supporting cast includes Lionel Barrymore as a Russian general besotted with her, Lewis Stone as an icy master spy, and Ramon Novarro as a handsome aviator who wins the heart Mata Hari did not know she possessed. With the world at war, love was her weapon. And the only men she couldn't seduce were the 12 in the firing squad that ended her tragic and tumultuous life"--Container.